Review of “A Vida Secreta das Cidades (The Secret Life of Cities)” by Mateus Soares de Azevedo - de Mello, Ricardo Garcia (UIN Sunan Gunung Djati Bandung, 2024)
“The Secret Life of Cities”, authored by Brazilian writer Mateus Soares de Azevedo, fathoms the unknown spiritual dimensions present in the culture, art and history of emblematic cities around the world. The analytical and contemplative work is carried out by the author in loco in symbolic cities belonging to six religious traditions – Sunni Islam, Shiite Islam, Buddhism, Catholicism, Protestantism, and Eastern Christianity. The author's modus operandi is not that of the voyeur, the adventurer, or the collector of novelties, but rather that of the pilgrim in search of knowledge.